Potential Therapeutic Targeting of Coronavirus Spike Glycoprotein Priming - Elisa Barile; Carlo Baggio; Luca Gambini; Sergey A. Shiryaev; Alex Y. Strongin; Maurizio Pellecchia (Molecules, 2020)
Processing of certain viral proteins and bacterial toxins by host serine proteases is a frequent and critical step in virulence. The coronavirus spike glycoprotein contains three (S1, S2, and S2′) cleavage sites that are processed by human host proteases. The exact nature of these cleavage sites, and their respective processing proteases, can determine whether the virus can cross species and the level of pathogenicity. Recent comparisons of the genomes of the highly pathogenic SARS-CoV2 and MERS-CoV, with less pathogenic strains (e.g., Bat-RaTG13, the bat homologue of SARS-CoV2) identified possible mutations in the receptor binding domain and in the S1 and S2′ cleavage sites of their spike glycoprotein. However, there remains some confusion on the relative roles of the possible serine proteases involved for priming. Using anthrax toxin as a model system, we show that in vivo inhibition of priming by pan-active serine protease inhibitors can be effective at suppressing toxicity. Hence, our studies should encourage further efforts in developing either pan-serine protease inhibitors or inhibitor cocktails to target SARS-CoV2 and potentially ward off future pandemics that could develop because of additional mutations in the S-protein priming sequence in coronaviruses.